Chapter 7 Overlooking women's lived realities How Tunisia's Truth and Dignity Commission dealt with the hijab ban - Destrooper, Tine (Taylor & Francis, 2023)
Arab Spring, Transitional Justice, North Africa, Anticorruption, Colonial Legacy, international involvement, Reparations, victim participation, youth leadership, activism, racial taboos